Long‐term efficacy and safety of biosimilar infliximab (CT‐P13) after switching from originator infliximab: open‐label extension of the NOR‐SWITCH trial. (12th April 2019) - Goll, G. L.; Jørgensen, K. K.; Sexton, J.; Olsen, I. C.; Bolstad, N.; Haavardsholm, E. A.; Lundin, K. E. A.; Tveit, K. S.; Lorentzen, M.; Berset, I. P.; Fevang, B. T. S.; Kalstad, S.; et al.
Abstract: Background and objectives: The 52‐week, randomized, double‐blind, noninferiority, government‐funded NOR‐SWITCH trial demonstrated that switching from infliximab originator to less expensive biosimilar CT‐P13 was not inferior to continued treatment with infliximab originator. The NOR‐SWITCH extension trial aimed to assess efficacy, safety and immunogenicity in patients on CT‐P13 throughout the 78‐week study period (maintenance group) versus patients switched to CT‐P13 at week 52 (switch group). The primary outcome was disease worsening during follow‐up based on disease‐specific composite measures. Methods: Patients were recruited from 24 Norwegian hospitals, 380 of 438 patients who completed the main study: 197 in the maintenance group and 183 in the switch group. In the full analysis set, 127 (33%) had Crohn's disease, 80 (21%) ulcerative colitis, 67 (18%) spondyloarthritis, 55 (15%) rheumatoid arthritis, 20 (5%) psoriatic arthritis and 31 (8%) chronic plaque psoriasis. Results: Baseline characteristics were similar in the two groups at the time of switching (week 52). Disease worsening occurred in 32 (16.8%) patients in the maintenance group vs. 20 (11.6%) in the switch group (per‐protocol set). Adjusted risk difference was 5.9% (95% CI −1.1 to 12.9). Frequency of adverse events, anti‐drug antibodies, changes in generic disease variables and disease‐specific composite measures were comparable between arms. The study was inadequately powered to detect noninferiority within individual diseases. Conclusion: The NOR‐SWITCH extension showed no difference in safety and efficacy between patients who maintained CT‐P13 and patients who switched from originator infliximab to CT‐P13, supporting that switching from originator infliximab to CT‐P13 is safe and efficacious. Abstract : Click here to view the Editorial comment by Dr. Kay